Komunikasi Kesehatan dalam Isu Kebijakan Publik: Analisis Tayangan YouTube 'Polemik Aturan BPJS 2025 - Solihin, Olih; Olih Solihin; Septri Widiono; Lovia Evanne (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2025)
This study analyzes health communication in the context of public policy through the YouTube video “Polemic on BPJS Regulation 2025” on the BeritaSatu channel. The main issue raised is the ineffectiveness of government communication in disseminating the new BPJS regulation, which triggered predominantly negative public responses. The objective of this research is to examine the government's communication narrative and public reactions expressed in the video comments. A descriptive qualitative approach was used, employing content and thematic analysis, supported by NVivo 12 software to systematically map public opinion. The findings show that negative sentiment dominates (69%), reflecting unclear policy information, public distrust, and anxiety over children’s health services. This study highlights the importance of responsive, participatory, and adaptive health communication strategies in digital media contexts. The findings offer theoretical implications for developing public policy communication and practical recommendations for government agencies to design public communication based on digital literacy and social trust.